Two new species of Tetralidia Marques-Costa & Cavichioli (Hemiptera: Cicadellidae: Neocoelidiinae) from Peru with a key to species of the genus - Gonçalves, Clayton Corrêa; Marques-Costa, Ana Paula (Zootaxa, 2014)
Two new species of Tetralidia Marques-Costa & Cavichioli, 2008: Tetralidia pachamama sp. nov. and Tetralidia viracocha sp. nov. are described and illustrated. T. pachamama sp. nov. can be distinguished from the other species of the genus by the simple aedeagus, without processes, spines or lamellae, while T. viracocha sp. nov. can be distinguished by the aedeagus with two pairs of lamellae at shaft and anal tube with basiventral processes strongly curved posteriorly. An identification key to males of the species is provided.